Investigating the Effectiveness of the Treffinger Learning Model in Teaching English: An Experimental Research - Baihaqi Baihaqi; Rahmah Fithriani; Pardi Pardi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Teaching of narrative writing requires instructional approaches that promote creativity and higher-order thinking. The treffinger learning model, which consists of Basic Tools, Practice with Process, and Working with Real Problems, offers a structured framework for developing students’ creative thinking in writing. This study investigated the effect of the Treffinger Learning Model on students’ narrative writing skills. A quasi-experimental design was employed involving two eighth-grade classes (N = 52) from a junior high school, assigned as an experimental group and a control group. Data were collected through pretest and posttest writing assessments in the form of essay tasks. The results showed that students’ initial writing ability was relatively low, with mean pretest scores of 34.42 (experimental) and 29.12 (control). Following the intervention, the experimental group demonstrated a substantially higher improvement, achieving a mean posttest score of 84.27, compared to 71.04 in the control group. The findings indicate that the Treffinger Learning Model contributes positively to the development of students’ narrative writing skills. This study highlights the pedagogical value of creativity-based learning models in English language classrooms.